Effect of Capital Structure and Audit Committee on Earnings Management during Covid-19 on Public Companies in the Pulp and Paper Sector - Hawila, Jennifer (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2022)
This study aims to determine whether the Capital Structur and Audit Committee have a significant effect on Earnings Management during Covid-19 on public companies in the pulp and paper . The type of data used in this research is quantitative data and the data source is secondary data. The population in this study are pulp and paper subsector manufacturing companies listed on the Indonesia Stock Exchange as many as 9 companies for the 2020-2021 period. The sample in this study were 7 companies with purposive sampling technique. Data analysis technique using multiple linear regression analysis method. This analysis includes descriptive statistics, classical assumption test, multiple regression analysis, hypothesis testing through t and F tests, and coefficient of determination test (R Square). From this analysis, it is obtained that the multiple linear regression equation Earnings Management = 627.384.190.200,000 - 10.948.787.110,000 Capital Structure – 1.628.729.107.000,000 Audit Committee + e. The results of partial research shows that the Capital Structure has no effet and no significant on Earnings Management in pulp and paper sub-sector manufacturing companies listed on the Indonesian Stock Exchange where the tcount value is -0,592 > ttable 2.004879 and significant value < 0,05 which is 0,557 < 0,05 and Audit Committee has no effect and no significant on Earnings Management in sub-manufacturing companies. pulp and paper sector which is listed on the indonesia stock exchange where the value of tcount is -0,536 < ttable 2,004879 and significant value > 0,05 which is 0.594 > 0.05 . The results of silmutaneous research shows that the Capital Stuctur and Audit Committee have no effect and no significant effect on on Earnings Management in pulp and paper sub-sector manufacturing companies listed on the Indonesian stock exchange where the value of Fcount is 2,236 > Ftable 3,17 and significant value < 0,05 which is 0,791 < 0,05. The results of the coefficient of determination (R Square) show that 0,9% of the dependent variable in Earnings Management can be explained by the Audit Committee and Auditor Independence. While the remaining 99,1% is explained by other variables not examined in this study such as company size, institutional ownership.